Violencia estructural y pecado original en René Girard = Abweichender Titel: Structural violence and original sin in René Girard - Buil Zamorano, Unai (Cauriensia, 2025)
Most studies about René Girard's Mimetic Theory sustain the idea that mimetic desire's natural dynamics of violent expansion ended up engendering a posteriori the scapegoat mechanism (whose core is sacrifice) as a means of salvation for society. In this paper, however, an interpretive alternative is offered, which is as follows. Sacrifice was not really an element that emerged merely a posteriori due to mimetic desire's violent consequences. Rather, mimetic desire’s violent traits are created by sacrifice, which planted them into mimetic desire a priori, as their ontological cause. In addition, it is claimed that, epistemologically speaking, there is an antecedence of the scapegoat mechanism over mimetic desire in the chronological context of Girard's Works, which is apparent when the term "mimetic desire" is coined in La Violence et le Sacré (1972) in a second moment of his intellectual evolution, after having discovered the scapegoat mechanism. In other words, mimetic desire flows into violence and death inevitably as it is destruction-oriented from the very beginning of human history, due to the influence of a special sacrifice that is represented by the scapegoat mechanism. That sacrifice was original sin.